Synthesis of the 1, 2-seco fusicoccane diterpene skeleton by Stille coupling reaction between the highly functionalized A and C ring segments of cotylenin A. Issue 41 (12th October 2017) - Kuwata, Kazuaki; Hanaya, Kengo; Higashibayashi, Shuhei; Sugai, Takeshi; Shoji, Mitsuru
Abstract: 1-Hydroxy-14-isopropyl-3β-methoxymethyl-7β, 11β-dimethyl-3α-[((2-trimethylsilyl)ethoxy)methoxy]-1, 2-secofusicocca-8, 10(14)-dien-2-one, a highly functionalized 1, 2-seco fusicoccane diterpene skeleton related to cotylenin A was synthesized in a convergent manner. The A ring segment, i. e ., (1′ R, 2 S, 2′ E, 5 S )-2-methoxymethyl-5-[1′-methyl-3'-(trimethylstannyl)prop-2-enyl]-2-[((2″-trimethylsilyl)ethoxy)methoxy]cyclopentanone, was synthesized in 20.1% yield over 18 steps from known ( S )-5-isopropenyl-2-methylcyclopent-1-enecarbaldehyde. This was coupled with the C ring segment, i. e ., ( R )-5-hydroxymethyl-2-isopropyl-5-methylcyclopent-1-en-1-yl trifluoromethylsulfonate, which was prepared according to our previous report. The Stille coupling reaction between alkenylstannane and sterically hindered triflate proceeded successfully in the presence of PEPPSI-SIPr (85%), and the total yield of the target molecule was 17.1% over the longest linear sequences (19 steps) from ( S )-5-isopropenyl-2-methylcyclopent-1-enecarbaldehyde. Graphical abstract: